High-strength porous polyaryletherketone foam material and preparation method thereof

By optimizing the components and processes of porous polyaryletherketone foam materials, and using hollow quartz fiber and supercritical carbon dioxide foaming technology, the problems of complex and poor strength of existing materials are solved, and the preparation of high-strength porous polyaryletherketone foam materials are realized, which is suitable for a variety of application scenarios.

CN119613941AInactive Publication Date: 2025-03-14CHANGZHOU TIANSHENG NEW MATERIALS RES INST CO LTD

Patent Information

Application Number
CN202411773880.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing porous polyaryletherketone foam materials have complex preparation processes and low porosity, resulting in poor material strength, which limits its scope of application.

Method used

By optimizing the components of the porous polyaryletherketone foam material, selecting polyaryletherketone resin, porous modified materials, nucleating agents and antioxidants for preparation, using hollow quartz fiber as reinforced filler, and high-strength porous polyaryletherketone foam material is prepared by supercritical carbon dioxide foaming technology.

Benefits of technology

It improves the strength, toughness and stability of the material, reduces the overall weight of the material, is suitable for applications in extreme environments, and shows excellent performance in different application occasions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613941A_ABST
    Figure CN119613941A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polyaryletherketone foam materials, in particular to a preparation method of a high-strength porous polyaryletherketone foam material. The high-strength porous polyaryletherketone foam material comprises the following substances in parts by weight: 80-95 parts of polyaryletherketone resin; 5-20 parts of a porous modified material; 0.1 to 1.0 part of a nucleating agent; 0.1 to 1.0 part of an antioxidant; the polyaryletherketone resin comprises at least one of polyether-ether-ketone resin, polyether-ketone-ketone resin and phenolphthalein polyaryletherketone resin. According to the technical scheme, the components of the porous polyaryletherketone foam material are optimized, the polyaryletherketone resin, the porous modified material, the nucleating agent and the antioxidant are selected for preparation, the strength and toughness of the material are improved through introduction of the porous modified material, the overall weight of the material is reduced, and the trend of modern lightweight design is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyaryletherketone foam materials, in particular to a method for preparing a high-strength porous polyaryletherketone foam material. Background Art

[0002] Polyaryletherketone (PAEK) foam is a type of high-performance special engineering plastic foam material. It has broad application prospects in aerospace, electronic equipment, artificial bones, military facilities, etc. due to its high strength, low dielectric, self-flammability, high temperature resistance, good biocompatibility, and excellent chemical stability. The preparation methods of polyaryletherketone porous foams currently mainly include blowing agent method, leaching method, melt deposition method, phase separation method, supercritical foaming method, etc. Usually, it is necessary to adopt a suitable preparation method according to the actual use conditions such as the pore size, porosity, and pore shape of the foam.

[0003] However, the porosity of the polyetheretherketone foamed materials prepared by the existing preparation of polyaryletherketone foam materials is low, which limits its application scenarios. In addition, some technical solutions require the use of dilute hydrochloric acid and concentrated sulfuric acid to remove the porogen and surface treatment during the preparation of porous polyaryletherketone materials, and repeated cleaning with deionized water. The product preparation cycle is long, the process is complicated, and the efficiency is low.

[0004] Therefore, the existing porous polyaryletherketone foam material has the defects of complex preparation process and poor strength of the prepared porous polyaryletherketone foam material, which greatly limits its scope of application. Summary of the invention

[0005] Based on the technical problems existing in the above-mentioned prior art, the present invention provides a high-strength porous polyaryletherketone foam material and a preparation method thereof.

[0006] In the first aspect, the present application provides a high-strength porous polyaryletherketone foam material, which adopts the following technical solution: A high-strength porous polyaryletherketone foam material comprises the following substances in parts by weight: 80-95 parts of polyaryletherketone resin; 5-20 parts of porous modified material; Nucleating agent 0.1-1.0 part; Antioxidant 0.1-1.0 part; The polyaryletherketone resin includes at least one of polyetheretherketone resin, polyetherketoneketone resin and phenolphthalein polyaryletherketone resin.

[0007] Through the above technical scheme, the technical scheme of the present application optimizes the components of the porous polyaryletherketone foam material, selects polyaryletherketone resin, porous modified material, nucleating agent and antioxidant for preparation, and the introduction of porous modified material not only improves the strength and toughness of the material, but also reduces the overall weight of the material, which is in line with the trend of modern lightweight design. The addition of nucleating agent and antioxidant can effectively improve the microstructure of the foam, increase the stability and service life of the material, so that the material can still maintain good mechanical properties under extreme environments. The diversity of polyaryletherketone resin (such as polyetheretherketone, polyetherketoneketone, etc.) provides flexibility for the performance adjustment of the material, so that it exhibits excellent performance in different applications.

[0008] Furthermore, the nucleating agent is a silicate nucleating agent with a particle size of 800-4000 meshes, and the silicate nucleating agent includes one or more of talc powder, kaolin, talcum powder and mica powder.

[0009] Through the above technical scheme, the technical scheme of the present application clarifies the type of nucleating agent, specifies the use of a silicate nucleating agent with a particle size of 800-4000 mesh, promotes the uniformity of the foam structure in the processing of porous polyaryletherketone foam materials, improves the pore structure of the foam, and then improves the strength and stability of the material. By optimizing the type and particle size of the nucleating agent, the porosity and distribution of the foam can be better controlled, and the physical properties of the enhanced material can be enhanced. In addition, since silicate nucleating agents have good chemical stability and high temperature resistance, they can maintain stable performance during high temperature processing. Therefore, the selection of this nucleating agent effectively improves the strength and heat resistance of the foam material, making it have better applicability in applications requiring high strength and high temperature resistance.

[0010] Furthermore, the antioxidant includes a hindered amine antioxidant 545 .

[0011] Furthermore, the porous modified material includes hollow quartz fibers with a hollowness of 20-60% and a length of 1-5 mm.

[0012] Through the above technical scheme, the technical scheme of this application emphasizes the use of porous modified materials, especially hollow quartz fibers. Hollow quartz fibers have excellent thermal insulation and mechanical properties, and can significantly improve the overall performance of foam materials. Because the hollowness of hollow quartz fibers is too low, the amount of air stored is small, and the porosity formed is low; the hollowness is too high, the strength of hollow quartz fibers decreases, and the reinforcing effect is reduced, so this application optimizes the hollowness of hollow quartz fibers between 20-60%, which is conducive to optimizing the density and strength of the material, while reducing the weight of the foam, in line with the lightweight design concept. Using hollow quartz fibers as reinforcing fillers, on the one hand, more than 99% of the components of hollow quartz fibers are SiO2, which has an extremely high tensile modulus and can effectively improve the mechanical properties of polyaryletherketone; on the other hand, there is air in the hollow part of the hollow quartz fibers. When polyaryletherketone is sintered at high temperature, the air expands and merges in the polyaryletherketone melt to form pores, further improving the porosity of porous polyaryletherketone foam materials.

[0013] Furthermore, the hollow quartz fiber is a surface-treated hollow quartz fiber, and the surface treatment includes the following technical solutions: The hollow quartz fiber is added into an ethanol aqueous solution, and then a silane coupling agent is added and stirred. After the stirring is completed, the fiber is allowed to stand for separation and then dried at 80-120° C. for 2-4 hours to obtain a surface-treated hollow quartz fiber.

[0014] Furthermore, the silane coupling agent includes at least one of silane coupling agent A-1110, silane coupling agent KH570 and silane coupling agent KH560, and the added amount of the silane coupling agent is 0.5-10wt% of the amount of the hollow quartz fiber.

[0015] Through the above technical scheme, the technical scheme of the present application preferably uses silane coupling agents such as A-1110, KH570 and KH560, which can produce -Si(OH)3 after hydrolysis and react with hollow quartz fibers to form stable siloxanes. The amino groups in the silane coupling agent combine with polyaryletherketone to form a stable interface, thereby increasing the interfacial compatibility between the hollow quartz fibers and polyaryletherketone, and improving the mechanical properties and durability of the composite material. Due to the small amount of silane coupling agent added, some hollow quartz fibers do not react with the coupling agent, reducing the interfacial compatibility in polyaryletherketone; if the amount of silane coupling agent added is too much, a coating will be formed on the surface of the hollow quartz fiber, reducing its interfacial adhesion in polyetheretherketone, so the present application can finely control the performance of the composite material by adjusting the amount of silane coupling agent added, and optimize its performance under different use environments. The use of silane coupling agents can not only enhance the moisture resistance and oxidation resistance of the material, but also improve the processability of the material, improve processing efficiency, and reduce production costs. The excellent compatibility of the modified hollow quartz fiber and polyaryletherketone resin can effectively improve the overall performance of the foam, making it more suitable for application requirements in high strength and special environments.

[0016] In the second aspect, the present application provides a method for preparing a high-strength porous polyaryletherketone foam material, using the following technical solution: A method for preparing a high-strength porous polyaryletherketone foam material comprises the following preparation steps: S1, mixing the porous modified material with a polyaryletherketone resin, a nucleating agent and an antioxidant to obtain a polyaryletherketone resin mixture; S2, loading the polyaryletherketone resin mixture into a mold, applying pressure and then maintaining pressure to prepare a molded plate; S3, placing the molded plate in a heating device, heating it up and sintering it at a constant temperature, and obtaining a pre-foamed plate after cooling; S4, placing the pre-foamed board in a molding foaming device for supercritical carbon dioxide foaming to prepare the high-strength porous polyaryletherketone foam material.

[0017] Through the above technical scheme, the technical scheme of this application first mixes the components by stirring to ensure the uniformity of the ingredients, which helps the uniformity and stability of the subsequent foaming. The molding and sintering process ensures that the material is fully compacted during molding, which improves the density and strength of the foam material. Finally, the supercritical carbon dioxide foaming method is not only environmentally friendly but also can achieve high-quality foam structure, further enhancing the performance of the material, making it show unique advantages in various applications. The preparation method is simple to operate, and the porosity and foaming ratio of the polyaryletherketone foam can be controlled by adjusting the amount of hollow quartz fiber and the supercritical foaming conditions.

[0018] Furthermore, the pressure of the pressure-maintaining treatment in step S2 is 20-120 MPa, and the pressure-maintaining time is 5-30 min.

[0019] Through the above technical scheme, the technical scheme of this application has made specific provisions for the pressure and time of the pressure holding treatment, which is crucial to the performance of the final material. Appropriate pressure holding treatment can ensure the density of the inside of the molded plate, avoid gaps and defects, and thus improve the strength and appearance quality of the material. Since the molded plate has poor density and is easy to break when the molding pressure is too low, and high pressure places high requirements on the equipment, this application can effectively adjust the microstructure of the foam material and optimize the performance by controlling the pressure holding pressure (20-120MPa) and time (5-30min). Such a process design makes the final product perform well in both physical and chemical properties, and has better application prospects.

[0020] Furthermore, the heating rate of step S3 is 50-200°C / h, the sintering temperature is 270-350°C, the sintering time is 0.5-5h, and the cooling treatment is cooling to a temperature not higher than 200°C.

[0021] Furthermore, the supercritical carbon dioxide foaming conditions described in step S4 include: The supercritical carbon dioxide has a foaming temperature of 250-280° C., a saturation pressure of 9-20 MPa, a saturation time of 0.5-3 h, and a pressure relief rate of 20-100 MPa / s.

[0022] Through the above technical solution, since the supercritical foaming temperature should be lower than the melting temperature, if the temperature is too low, the melt viscosity is high, the resistance of the cell growth is too large, resulting in too low foaming ratio; if the temperature is too high, the cells are easy to break and merge, resulting in a decrease in the mechanical properties of the foam, so this application can effectively adjust the microstructure of the foam material and optimize the performance by controlling the holding pressure (9-20MPa) and time (0.5-3h). Such a process design makes the final product perform well in both physical and chemical properties and has better application prospects.

[0023] In summary, this application has the following beneficial effects: First, the technical solution of this application optimizes the components of porous polyaryletherketone foam materials, selects polyaryletherketone resin, porous modified materials, nucleating agents and antioxidants for preparation, and the introduction of porous modified materials not only improves the strength and toughness of the material, but also reduces the overall weight of the material, which is in line with the trend of modern lightweight design. The addition of nucleating agents and antioxidants can effectively improve the microstructure of the foam, increase the stability and service life of the material, so that the material can still maintain good mechanical properties under extreme environments. The diversity of polyaryletherketone resins (such as polyetheretherketone, polyetherketoneketone, etc.) provides flexibility for the performance adjustment of the material, allowing it to exhibit excellent performance in different applications.

[0024] Second, the technical solution of this application emphasizes the use of porous modified materials, especially hollow quartz fibers. Hollow quartz fibers have excellent thermal insulation and mechanical properties, and can significantly improve the overall performance of foam materials. The design of hollowness between 20-60% is conducive to optimizing the density and strength of the material, while reducing the weight of the foam, which is in line with the lightweight design concept. Hollow quartz fibers are used as reinforcing fillers. On the one hand, more than 99% of the components of hollow quartz fibers are SiO2, which has an extremely high tensile modulus and can effectively improve the mechanical properties of polyaryletherketone; on the other hand, there is air in the hollow part of the hollow quartz fiber. When polyaryletherketone is sintered at high temperature, the air expands and merges in the polyaryletherketone melt to form pores, further improving the porosity of the porous polyaryletherketone foam material.

[0025] Third, the technical solution of this application first mixes the components by stirring to ensure the uniformity of the ingredients, which helps the uniformity and stability of the subsequent foaming. The molding and sintering process ensures that the material is fully compacted during molding, which improves the density and strength of the foam material. Finally, the supercritical carbon dioxide foaming method is not only environmentally friendly but also can achieve high-quality foam structure, further enhancing the performance of the material, making it show unique advantages in various applications. The preparation method is simple to operate, and the porosity and foaming ratio of the polyaryletherketone foam can be controlled by adjusting the amount of hollow quartz fiber and the supercritical foaming conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of the high-strength porous polyaryletherketone foam material prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0027] The present application is further described in detail below with reference to the embodiments.

[0028] In the examples of the present application, the raw materials and instruments used are as follows, but not limited thereto. Raw materials not otherwise specified are of analytical grade.

[0029] Preparation Example 1 Take 100 g of hollow quartz fiber and add it to 500 mL of 80% ethanol aqueous solution at 80°C, then add 5 mL of silane coupling agent A-1110, stir at 80°C for 4 hours, filter and separate the hollow quartz fiber in the solution, and dry at 100°C for 2 hours to prepare a surface-treated hollow quartz fiber.

[0030] Example 1 A high-strength porous polyaryletherketone foam material comprises 12.5g of surface-treated hollow quartz fiber, 238g of phenolphthalein polyaryletherketone PEKC, 0.25g of talc powder and 0.25g of antioxidant 545.

[0031] A method for preparing a high-strength porous polyaryletherketone foam material comprises the following preparation steps: S1. Mix 238 g of phenolphthalein poly(aryletherketone) PEKC, 12.5 g of the surface-treated hollow quartz fiber prepared in step 1 of Example 1, 0.25 g of talcum powder, and 0.25 g of antioxidant 545 in a high-speed mixer for 5 min.

[0032] S2. Add the above mixture into the mold, pressurize to 60MPa at room temperature and maintain the pressure for 10 minutes. After the pressure maintenance is completed, release the pressure to 0MPa and take out the molded plate.

[0033] S3, putting the molded plate into an oven, raising the temperature to 300°C at a heating rate of 150°C / h, sintering at this temperature for 2h, cooling to 180°C after sintering, and taking out to obtain a pre-foamed plate.

[0034] S4. Place the pre-foamed board into a compression foaming device for supercritical carbon dioxide foaming. The foaming conditions are as follows: a foaming temperature of 280° C., a carbon dioxide saturation pressure of 11 MPa, a saturation time of 2 h, and a pressure relief rate of 50 MPa / s.

[0035] Example 2 A high-strength porous polyaryletherketone foam material comprises 25g of surface-treated hollow quartz fiber, 225g of phenolphthalein polyaryletherketone PEKC, 0.25g of talcum powder and 0.25g of antioxidant 545.

[0036] A method for preparing a high-strength porous polyaryletherketone foam material comprises the following preparation steps: S1. Mix 225 g of phenolphthalein poly(aryletherketone) PEKC, 25 g of the surface-treated hollow quartz fiber prepared in step 1, 0.25 g of talc powder, and 0.25 g of antioxidant 545 in a high-speed mixer for 5 min.

[0037] S2. Add the above mixture into the mold, pressurize to 60MPa at room temperature and maintain the pressure for 10 minutes. After the pressure maintenance is completed, release the pressure to 0MPa and take out the molded plate.

[0038] S3, putting the molded plate into an oven, raising the temperature to 300°C at a heating rate of 150°C / h, sintering at this temperature for 2h, cooling to 180°C after sintering, and taking out to obtain a pre-foamed plate.

[0039] S4. Place the pre-foamed board into a compression foaming device for supercritical carbon dioxide foaming. The foaming conditions are as follows: a foaming temperature of 270° C., a carbon dioxide saturation pressure of 10 MPa, a saturation time of 2 h, and a pressure relief rate of 50 MPa / s.

[0040] Example 3 A high-strength porous polyaryletherketone foam material comprises 37.5g of surface-treated hollow quartz fiber, 211.5g of phenolphthalein polyaryletherketone PEKC, 0.5g of talc powder and 0.5g of antioxidant 545.

[0041] A method for preparing a high-strength porous polyaryletherketone foam material comprises the following preparation steps: S1. Mix 211.5 g of phenolphthalein poly(aryletherketone) PEKC, 37.5 g of the surface-treated hollow quartz fiber prepared in step 1 of Example 1, 0.5 g of talcum powder, and 0.5 g of antioxidant 545 in a high-speed mixer for 5 min.

[0042] S2. Add the above mixture into the mold, pressurize to 60MPa at room temperature and maintain the pressure for 10 minutes. After the pressure maintenance is completed, release the pressure to 0MPa and take out the molded plate.

[0043] S3, putting the molded plate into an oven, raising the temperature to 290°C at a heating rate of 150°C / h, sintering at this temperature for 3h, cooling to 180°C after sintering, and taking out to obtain a pre-foamed plate.

[0044] S4. Place the pre-foamed board into a compression foaming device for supercritical carbon dioxide foaming. The foaming conditions are as follows: a foaming temperature of 260° C., a carbon dioxide saturation pressure of 10 MPa, a saturation time of 2 h, and a pressure relief rate of 50 MPa / s.

[0045] Example 4 S1. Mix 225 g of phenolphthalein poly(aryletherketone) PEKC, 25 g of hollow quartz fiber without surface treatment, 0.25 g of talc powder and 0.25 g of antioxidant 545 in a high-speed mixer for 5 min.

[0046] S2. Add the above mixture into the mold, pressurize to 60MPa at room temperature and maintain the pressure for 10 minutes. After the pressure maintenance is completed, release the pressure to 0MPa and take out the molded plate.

[0047] S3, putting the molded plate into an oven, raising the temperature to 290°C at a heating rate of 150°C / h, sintering at this temperature for 2h, cooling to 180°C after sintering, and taking out to obtain a pre-foamed plate.

[0048] S4. Place the pre-foamed board into a compression foaming device for supercritical carbon dioxide foaming. The foaming conditions are as follows: a foaming temperature of 260° C., a carbon dioxide saturation pressure of 10 MPa, a saturation time of 2 h, and a pressure relief rate of 50 MPa / s.

[0049] Comparative Example 1 S1. Mix 250 g of phenolphthalein poly(aryletherketone) PEKC, 0.25 g of talc and 0.25 g of antioxidant 545 in a high-speed mixer for 5 min.

[0050] S2. Add the above mixture into the mold, pressurize to 60MPa at room temperature and maintain the pressure for 10 minutes. After the pressure maintenance is completed, release the pressure to 0MPa and take out the molded plate.

[0051] S3, putting the molded plate into an oven, raising the temperature to 300°C at a heating rate of 150°C / h, sintering at this temperature for 2h, cooling to 180°C after sintering, and taking out to obtain a pre-foamed plate.

[0052] S4. Place the pre-foamed board into a compression foaming device for supercritical carbon dioxide foaming. The foaming conditions are as follows: a foaming temperature of 280° C., a carbon dioxide saturation pressure of 11 MPa, a saturation time of 2 h, and a pressure relief rate of 50 MPa / s.

[0053] It should be noted that the polyaryletherketone resin used in the present application includes at least one of polyetheretherketone resin, polyetherketoneketone resin, and phenolphthalein polyaryletherketone resin.

[0054] The nucleating agent used in the present application is a silicate nucleating agent with a particle size of 800-4000 meshes, and the silicate nucleating agent includes one or more of talc powder, kaolin, talcum powder and mica powder.

[0055] Performance Testing The porous polyaryletherketone foam materials prepared in Examples 1-4 and Comparative Example 1 were subjected to performance tests: Compression strength: The compression test is carried out in accordance with the standard GB / T 8813-2020 Determination of compression properties of rigid foam plastics. The compression strength of the sample is the quotient of the maximum compression force obtained when the relative deformation is 10% divided by the initial area of ​​the sample cross section.

[0056] Bending strength: Tested in accordance with standard GB / T 8812-2007, the method for determining the bending properties of rigid foam plastics.

[0057] Porosity: First measure the volume and mass of the sample, and calculate the porosity according to the following formula:

[0058] Where: M is the sample mass (g), V is the sample volume (cm3), and ρs is the density of PEKC dense solid (1.25 g / cm3).

[0059] Foaming ratio: the ratio of the density of PEKC dense solid to the density of the prepared sample.

[0060] The results are shown in Table 1 below: Table 1 Performance test table

[0061] From the above examples 1-4 and comparative example 1, combined with Table 1 and Figure 1 By comparing the test results, we can find that: Depend on Figure 1 It can be seen that the porous polyaryletherketone foam material prepared in the present application has a uniform porous structure with an average pore diameter of 43 μm, and hollow quartz fibers are interspersed therein.

[0062] By comparing Examples 1-3 with Example 4, since a porous material of hollow quartz fibers without surface treatment is added in Example 4, although its porosity does not change significantly, its strength is significantly reduced, indicating that the technical solution of the present application preferably couples the silane coupling agent with the hollow quartz fibers to form a stable interface, thereby increasing the interfacial compatibility between the hollow quartz fibers and the polyaryletherketone, and improving the mechanical properties and durability of the composite material.

[0063] By comparing Examples 1-4 with Comparative Example 1, it can be further found that since the porous material of hollow quartz fiber is not added in the technical scheme of Comparative Document 1, its compressive strength, porosity and foaming ratio are significantly reduced, which further illustrates that the technical scheme of the present application can effectively improve the mechanical properties of polyaryletherketone by adding surface-treated hollow quartz fiber. At the same time, there is air in the hollow part of the hollow quartz fiber. When polyaryletherketone is sintered at high temperature, the air expands and merges in the polyaryletherketone melt to form pores, thereby further improving the porosity of the porous polyaryletherketone foam material.

[0064] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0065] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0066] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0067] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

Claims

1. A high-strength porous polyaryletherketone foam material, characterized in that: The composition includes the following materials in parts by weight: 80-95 parts of polyaryletherketone resin; 5-20 parts of porous modified material; Nucleating agent 0.1-1.0 part; Antioxidant 0.1-1.0 part; The polyaryletherketone resin includes at least one of polyetheretherketone resin, polyetherketoneketone resin and phenolphthalein polyaryletherketone resin.

2. A high-strength porous polyaryletherketone foam material according to claim 1, characterized in that: The nucleating agent is a silicate nucleating agent with a particle size of 800-4000 meshes, and the silicate nucleating agent includes one or more of talc powder, kaolin, talcum powder and mica powder.

3. The high-strength porous polyaryletherketone foam material according to claim 1, characterized in that: The antioxidant includes hindered amine antioxidant 545.

4. The high-strength porous polyaryletherketone foam material according to claim 1, characterized in that: The porous modified material includes hollow quartz fibers with a hollowness of 20-60% and a length of 1-5 mm.

5. A high-strength porous polyaryletherketone foam material according to claim 4, characterized in that: The hollow quartz fiber is a surface-treated hollow quartz fiber, and the surface treatment includes the following technical solutions: The hollow quartz fiber is added into an ethanol aqueous solution, and then a silane coupling agent is added and stirred. After the stirring is completed, the fiber is allowed to stand for separation and then dried at 80-120° C. for 2-4 hours to obtain a surface-treated hollow quartz fiber.

6. A high-strength porous polyaryletherketone foam material according to claim 5, characterized in that: The silane coupling agent includes at least one of silane coupling agent A-1110, silane coupling agent KH570 and silane coupling agent KH560, and the added amount of the silane coupling agent is 0.5-10wt% of the amount of the hollow quartz fiber.

7. A method for preparing a high-strength porous polyaryletherketone foam material according to any one of claims 1 to 6, characterized in that: The method comprises the following preparation steps: S1, mixing the porous modified material with a polyaryletherketone resin, a nucleating agent and an antioxidant to obtain a polyaryletherketone resin mixture; S2, loading the polyaryletherketone resin mixture into a mold, applying pressure and then maintaining pressure to prepare a molded plate; S3, placing the molded plate in a heating device, heating it up and sintering it at a constant temperature, and obtaining a pre-foamed plate after cooling; S4, placing the pre-foamed board in a molding foaming device for supercritical carbon dioxide foaming to prepare the high-strength porous polyaryletherketone foam material.

8. The method for preparing a high-strength porous polyaryletherketone foam material according to claim 7, characterized in that: The pressure of the pressure-maintaining treatment in step S2 is 20-120 MPa, and the pressure-maintaining time is 5-30 min.

9. The method for preparing a high-strength porous polyaryletherketone foam material according to claim 7, characterized in that: In step S3, the heating rate is 50-200°C / h, the sintering temperature is 270-350°C, the sintering time is 0.5-5h, and the cooling treatment is cooling to a temperature not higher than 200°C.

10. The method for preparing a high-strength porous polyaryletherketone foam material according to claim 7, characterized in that: The supercritical carbon dioxide foaming conditions described in step S4 include: The supercritical carbon dioxide has a foaming temperature of 250-280° C., a saturation pressure of 9-20 MPa, a saturation time of 0.5-3 h, and a pressure release rate of 20-100 MPa / s.

Citation Information

Patent Citations

  • Poly aryl ether ketone composite material and preparing method thereof

    CN107412848A

  • Polyether-ether-ketone porous foam material and preparation method thereof

    CN110527129A

  • Fiber-reinforced polyaryletherketone composite open-cell foam as well as preparation method and application thereof

    CN116640433A

  • Thermoplastic prepregs and composites

    GB2585875A

  • Foam molded article

    JP2009155366A

Cited By

  • PBAT foaming material and preparation method and application thereof

    CN121652446A